KERAGAAN USAHATANI PETANI MISKIN PADA LAHAN KERING DAN SAWAH TADAH HUJAN (STUDI KASUS DI KABUPATEN TEMANGGUNG) - ZAKARIA, AMAR K.; SWASTIKA, DEWA K.S. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005)
The Performance of Poor Farmers' Farming in Dryland and Rainfed Lowland: (The Case Study in Temanggung, Central Java). The Poor Farmers Income Improvement Through Innovation Project (PFI3P) is aimed to introduce some innovation for poor farmers, to enable them to solve their own problems. The project will provide them with appropriate agricultural technology as well as development of infrastructure facilities. Temanggung is one among five districts in Indonesia that granted ADB-funded Project for empowerment of poor farmers. Before project been implanted, the baseline survey was conducted. The objective of the survey is to get better understanding regarding social economic condition of involved farmers, in advance to PFI3P implementation. The survey took place in five villages, and 30 farmers in each village were chosen as samples. The results of the study showed that the return cost ratio (R/C) for rice farming was 1.28, meaning that every single rupiah spent for rice farming the gross return was 1.28. Meanwhile, the R/C ratio for corn was 1.27. These relatively low R/C were mainly due to low yield of both rice and corn. On the other hands, the R/C for chili and tobacco were 2.82 and 2.60, respectively, indicating high profit earned from these two case crops. Therefore, the contributions of these crops to the household income were relatively high compared to food crops.
Keywords: iIncome, Farming, Poor Farmers, Rainfed Lowland.